Integrating cybersecurity and artificial intelligence into tertiary education pedagogy - Todorova Natalia (Закарпатський угорський інститут імені Ференца Ракоці II, 2024)
Abstract. In today’s interconnected digital world, cybersecurity threats continue to evolve, posing serious risks to personal privacy, organizational integrity, and national security. AI technologies are being employed across industries, not only to drive innovation but also to combat these cybersecurity challenges. However, there is a significant gap in how tertiary education prepares students to tackle these issues. Most academic programs still treat cybersecurity and AI as niche technical subjects rather than as integral components of a broader educational framework. This separation restricts students' ability to develop their digital literacy, critical thinking, and ethical reasoning necessary to face real-world challenges.
Keywords: artificial intelligence; cybersecurity; tertiary education